2017
DOI: 10.1007/s11032-017-0764-z
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of main effect and epistatic quantitative trait loci for morphological and yield-related traits in peanut (Arachis hypogaea L.)

Abstract: An effort was made in the present study to identify the main effect and epistatic quantitative trait locus (QTL) for the morphological and yield-related traits in peanut. A recombinant inbred line (RIL) population derived from TAG 24 × GPBD 4 was phenotyped in seven environments at two locations. QTL analysis with available genetic map identified 62 main-effect QTLs (M-QTLs) for ten morphological and yieldrelated traits with the phenotypic variance explained (PVE) of 3.84-15.06%. Six major QTLs (PVE > 10%) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…The developed data could be utilized in functional genomics research to pin-point targeted candidate genes in groundnut. Trait mapping efforts led to identification of associated genomic regions for several important traits in groundnut including biotic and abiotic stresses, agronomic, yield component and oil quality traits (Agarwal et al, 2018;Khedikar et al, 2018;Pandey et al, 2012Pandey et al, , 2016Pandey et al, , 2017Varshney et al, 2013;Vishwakarma et al, 2017). Most of these studies identified mere loosely associated markers.…”
Section: Discussionmentioning
confidence: 99%
“…The developed data could be utilized in functional genomics research to pin-point targeted candidate genes in groundnut. Trait mapping efforts led to identification of associated genomic regions for several important traits in groundnut including biotic and abiotic stresses, agronomic, yield component and oil quality traits (Agarwal et al, 2018;Khedikar et al, 2018;Pandey et al, 2012Pandey et al, , 2016Pandey et al, , 2017Varshney et al, 2013;Vishwakarma et al, 2017). Most of these studies identified mere loosely associated markers.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic mapping of peanut yield components has led to the discovery of multiple quantitative trait loci (QTL) for pod and seed size traits including 100_pod_wt, 100_seed_wt, pod length, pod width, seed length, and seed width (Chen et al 2017;Fonceka et al 2012;Hake et al 2017;Khedikar et al 2018;Luo et al 2018;Luo et al 2017;Wang et al 2018). The number of QTL for pod and seed traits ranged from 1 to 92 suggesting that they have a complex genetic architecture.…”
Section: Introductionmentioning
confidence: 99%
“…These genotype data together with the phenotype data that are collected from the analyzed accessions were used to perform GWAS analyses for identifying genomic regions that are significantly associated with seven peanut yield-related traits. The identified associated regions were then compared to the QTL loci reported in earlier QTL mapping/GWAS studies (using different sets of peanut accessions comparing to the present study) [6,7,9,12,13,14], and co-localized regions received close examination.…”
Section: Introductionmentioning
confidence: 96%
“…Yield-related traits, such as hundred-seed/pod weight and mature pod number per plant, are mostly quantitative traits, which have been found to be governed by multiple loci and are influenced by environmental factors [5,6]. Understanding the genetic base of yield-related traits is the most important prerequisite for peanut genetic improvement and such understanding has been greatly advanced, especially through approaches that search for quantitative trait loci (QTL).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation